2021
DOI: 10.1155/2021/7029514
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Retinol-Binding Protein 4 and Markers of Inflammation and Thrombogenesis in Children with Kawasaki Disease

Abstract: Background. Kawasaki disease (KD) is a self-limited vasculitis with unknown etiologies, and coronary artery lesions (CALs) are the most common and serious complications. Retinol-binding protein 4 (RBP4) has been confirmed effects on vasodilation, platelet activation inhibition, and cardiovascular diseases by researches. Therefore, this study was aimed at investigating the relationship between RBP4 and inflammation as well as thrombogenesis in children with KD. Methods. 79 subjects were from 62 children with KD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…There is growing evidence that both innate and adaptive immune cells mediate the systemic and tissue-specific effects of KD-like CA aneurysms [9]. In light of this, several studies have suggested that NLR calculation may aid in the clinical assessment of the inflammatory aspect of KD, serving as a metric for risk stratification and prediction for adverse cardiac events in adulthood [13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence that both innate and adaptive immune cells mediate the systemic and tissue-specific effects of KD-like CA aneurysms [9]. In light of this, several studies have suggested that NLR calculation may aid in the clinical assessment of the inflammatory aspect of KD, serving as a metric for risk stratification and prediction for adverse cardiac events in adulthood [13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, 17 articles with 6334 KD patients, of whom 1328 developed CAA, were enrolled in this meta-analysis [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The list of included studies is shown in supplementary file B.…”
mentioning
confidence: 99%
“…Kimura et al showed that RBP4, which is a candidate diagnostic marker, was decreased in patients with acute KD 24 . Recently, Yang et al reported that KD patients had signi cantly lower RBP4 levels than healthy controls, suggesting that RBP4, which is a main retinol transport protein, is closely associated with markers of in ammation and thrombogenesis in children with KD 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanisms are poorly understood, RBP4 was suggested to modulate the crosstalk between AT dysfunction and the development of cancer [ 308 ]. Indeed, RBP4 is associated with the enhanced thrombogenicity of procoagulant states and knocking down RBP4 inhibits the growth of PC-3 cells in vitro [ 309 , 310 , 311 ]. Therefore, the possible roles of RBP4 at the intersection of these pathologies warrants further investigation.…”
Section: Periprostatic Adipose Tissue Secretome and Prostate Cancer P...mentioning
confidence: 99%